KONTRIBUSI TK/TPA DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATERI ALQURAN DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 247 PADATUO KEC. TONRA KAB. BONE. - Nuryani, Nuryani; Halidin, Ali (JURNAL AL-QAYYIMAH, 2021)
This paper discusses “The Contribution of TK/TPA in Increasing Students' Interest in Learning Al-Quran in Islamic Religious Education Subjects at SDN 247 Padatuo Kec. Tonra Kab. Bones". This study aims to describe the participation of students at SDN 247 Padatuo at TKA/TPA, and to determine students' interest in learning about the Qur'anic material in PAI subjects at SDN 247 Padatuo Kec. Tonra Kab. Bones. This research is a field research with the type of qualitative research, namely examining and researching respondents' sources found directly in the field through the results of observations, interviews and documentation. The approaches in this thesis are psychological approaches, pedagogical approaches and sociological approaches. Data processing techniques with data reduction, presentation or display of data and drawing conclusions. The data analysis techniques used are participation, persistence and triangulation. The results showed that the participation of TK/TPA students had contributed to Koranic education from an early age to students at SDN 247 Padatuo. Another contribution is to foster the interest of students to explore the Qur'anic material in PAI subjects at SDN 247 Padatuo.